Decentralisation of bargaining and manufacturing employment: Sweden 1970-96 - Anders Forslund; Thomas Lindh (Institute for Labour Market Policy Evaluation (IFAU), 2004)
Swedish unemployment was very low up to the early 1990s when it rose rapidly. At the same time manufacturing employment fell by more than 20 %. The decentralisation of wage bargaining that started in 1983 may have contributed to this by making employment more shock sensitive or by increasing wage mark-ups. In Swedish plant-level data for manufacturing 197096 relatively less employment is in low-productivity plants after decentralisation than before, but the correlation between industry wage costs and productivity becomes stronger. Our conclusion is that decentralisation of bargaining in Sweden has not allowed more low-productivity plants in manufacturing to survive. On the contrary, the evidence indicates that a higher wage mark-up may have resulted from the decentralisation. This would weed out low-productivity plants and decrease manufacturing employment.
Keywords: E24; J31; L60; 330; Manufacturing employment; bargaining institutions; industry structure